(untitled) (Research, Society and Development, 2021)
Modern medicine considers the intestine as the second brain, so it is of paramount importance for both the digestive and immune systems. Thus, an intestinal imbalance can cause several dysfunctions, among which, intestinal dysbiosis stands out. In this context, nutrition makes a relevant role with regard to intestinal homeostasis. Therefore, a bibliographic review was done on the subject. Through research, it was possible to realize that some factors can be attributed to the alteration of the microbiota, such as the type of child-birth, type of breastfeeding, adequate food introduction at the moment recommended by the World Health Organization (WHO), around six months. In view of this, it can be stated that the deficit in colonization and the profile of the intestinal microbiota acquired in childhood is difficult to reverse after two years, being able to impact in the neurocognitive development, growth and the appearing of diseases.